PENGOLAHAN LIMBAH JERAMI PADI MENGGUNAKAN TEKNOLOGI AMONIASI UNTUK PAKAN TERNAK RUMINANSIA DI NAGARI UJUNG GADING, PASAMAN BARAT (LPPM Universitas Andalas, 2022)
The primary feed source for ruminants is forage, which must be available in sufficient quantities. However, sometimes in the long dry season in Ujung Gading, West Pasaman, this forage is challenging to find. One source of feed that has not been utilized is rice straw. Straw is part of the rice stem without roots. Giving rice straw directly to livestock has low digestibility and low nutritional value. The objectives of this activity are 1. to improve the knowledge and skills of farmers in processing rice straw as quality animal feed from agricultural waste and 2. to develop the ammonia technology of straw as feed for ruminants. This activity has been carried out in Nagari Ujung Gading, Lembah Melintang District, West Pasaman Regency. The targets of this activity are farmers and the community in Nagari Ujung Gading, West Pasaman. The method of implementing the activities are socialization, training, and evaluation. The result of the implementation of the exercise is that there is an improvement in farmers' understanding and skills in rice straw processing using straw ammoniation technology as animal feed. The processing of agricultural waste in the form of ammoniated rice straw aims to improve the knowledge and skills of farmers in processing rice straw as quality animal feed from agricultural waste. Using straw ammonia technology aims to improve feed quality and digestibility for ruminants. This ammonia technique is easy to do, inexpensive, and does not pollute the environment. From the activity results, it can be concluded that rice straw ammoniation technology using urea can increase the nutritional value of rice straw as animal feed. The ammoniated rice straw can increase the energy value of the feed and effectively remove the microorganism contamination found in the rice straw.